A Proposed Framework for Curriculum Implementation: Tobacco Cessation in Dental Education - Sanikop, Sheetal (Disease and Health Research: New Insights Vol. 9, 2024)
Tobacco addiction is responsible for premature death and is an important cause of preventable death in the world. It is well established that tobacco use leads to a high risk of tobacco addiction-related diseases thus causing enormous morbidity and mortality of the human population. Clinicians should offer a brief intervention to every patient who uses tobacco, regardless of their willingness to quit. All health professionals generally should counsel their patients who are tobacco users to quit the habit. Dental students generally report feeling unprepared to counsel their tobacco-using patients to quit. This is because of the drawbacks of a lack of knowledge and confidence in the effectiveness of such tobacco cessation measures. Thus, the introduction of special systematic training as a part of the dental curriculum would overcome these drawbacks and equip dental graduates to deal with tobacco-addicted patients. To introduce and implement any new program within the curriculum, there has been a standard protocol followed. Therefore, this article suggests the use of Kern’s six steps/rules for the implementation of the Tobacco Cessation Program (TCP) within the dental curriculum. The six steps are namely: 1) Problem Identification and General Needs Assessment. 2) Needs assessment for targeted learners. 3) Goals and Objectives. 4) Educational Strategies. 5) Implementation. 6) Evaluation and Feedback. Step four is: 4) Developing educational Strategies will be the suggested methodology to introduce the TCP for dental undergraduates. Hence, this article aims to suggest a systematic TCP for dental undergraduates in their educational curriculum so that dental students become competent in performing tobacco cessation in their patients.